Cascade Reactions of Indigo with an Allenylic Reactant - Dyah U. C. Rahayu; Christopher Richardson; John B. Bremner; Paul A. Keller (Molecules, 2025)
The base-enabled reaction of buta-2,3-dien-1-yl methanesulfonate with the readily available and cheap dye indigo resulted in the convenient one-pot synthesis of benzoindolonaphthyridinedione and benzoazepinopyridoindolediones, with the latter representing two novel heterocyclic scaffolds. Despite the low yields, the allenylic alkylation of indigo significantly contributes to the new chemistry of this compound, providing new mechanistic insights and reactivity boundaries.